BUDAYA LOKAL PACITAN âTETAKENâ SEBAGAI SUMBER BELAJAR (STUDI KASUS MAHASISWA PENDIDIKAN SEJARAH DI STKIP PGRI PACITAN) - Iriyanti, Sri; Poerwanti, Endah Sri; Ratnasari, Sri Dwi (Jurnal Humaniora, 2014)
This research aims to describe about ceremonial âTetakenâ wich is one of the local culture in Pacitan. Traditional ceremony âTetakenâ is the welcoming ceremony by the village community districts Mantren who do meditation on Gunung Lima. The event is a form gratitude to Allah SWT for prosperity, ayem tentrem and loh jinawi around the mountain. Traditional ceremony âTetakenâ contains the values of social life wich serve as a source of learning, especially for students of history education of STKIP PGRI Pacitan. The challenge remains to technical constraints related to time, geography and myths about Gunung Lima. Optimizing the utilization of learning resources can be done through direct learning strategiesÂ with interactive multimedia, direct observation, assignment and presentation.Â Â Â Â Â Â Kata kunci : Local culture, Pacitan, Tetaken, Learning resources